Instructive feedback embedded within group instruction for children diagnosed with autism spectrum disorder. Issue 2 (17th February 2017) - Leaf, Justin B.; Cihon, Joseph H.; Alcalay, Aditt; Mitchell, Erin; Townley‐Cochran, Donna; Miller, Kevin; Leaf, Ronald; Taubman, Mitchell; McEachin, John
Abstract : The present study evaluated the effects of instructive feedback embedded within a group discrete trial teaching to teach tact relations to nine children diagnosed with autism spectrum disorder using a nonconcurrent multiple‐baseline design. Dependent variables included correct responses for: primary targets (directly taught), secondary targets (taught via instructive feedback), primary observational targets (directly taught to other members of the group), and secondary observational targets (taught via instructive feedback provided to other members of the group). Results showed that all nine participants reached the mastery criterion for the primary targets, as well as acquired the secondary and observational targets without direct teaching. Clinical implications and areas for future research are provided.